Erratum: DONGBIAO LÜ, YANHUA YAN, WEIHAI LI & HONGLIANG WANG (2019) A new species of the genus Chinoperla (Plecoptera: Perlidae) from southern China. Zootaxa, 4614: 187–190. - Lü, Dongbiao; Yan, Yanhua; Li, Weihai; Wang, Hongliang (Zootaxa, 2019)
N/A